Interrelation of Proctodrilus species (Oligochaeta: Lumbricidae) with lessivage and layering in European soil profiles - Höser, Norbert (Zootaxa, 2018)
The objective of this paper is to relate species occurrences of the earthworm genus Proctodrilus to soil properties, in particular the horizons and layers in the soil profile. Data on the occurrence in the soil profile of the earthworm species Proctodrilus antipai (Michaelsen, 1891), P. opisthoductus Zicsi, 1985, P. thaleri Höser & Zicsi 2009, and P. tuberculatus (Černosvitov, 1935) were collected in central Germany, northern Bohemia, Hungary, and Romania. Species of Proctodrilus were collected from 138 sites in total, P. antipai from 48, P. opisthoductus from 24, P. thaleri from 4, and P. tuberculatus from 97 sites. The field data show that species inhabiting the same site do not form communities but rather inhabit different soil layers. Furthermore, species of Proctodrilus prefer to live close to the boundaries between layers, a feature that can be regarded as a taxonomic characteristic of the genus and that is probably connected with their enteronephric excretory system. The habitats of the different species differ in the degree of soil leaching. P. thaleri and P. opisthoductus are restricted to the region of recent lessivage in warm-humid parts of Europe. Occurrence of the four Proctodrilus species is therefore not related to soil type but rather to soil stratification and soil leaching. Differences in the ecological behaviour of the species can be understood as taxonomic characters.